Velocity model of the mantle structure under Sumatra and seismic activity of the area - A. V. Kendzera; L. N. Zayets; T.A. Tsvetkova; A. N. Ostrovnoy (Геофизический журнал, 2014)
Within the framework of a three-dimensional P-velocity model of the mantle of the South-East Asia, the mantle velocity structure beneath Sumatra and its surroundings has been considered with the identification of possible premises in the deep structure of the mantle for manifestation of earthquakes in the region. The model has been obtained by application of the method of Taylor approximation for solution of seismic tomography problem of P-waves arrival time introduced by V. S. Geiko.